CLINICAL SYMPTOMATOLOGY OF COVID-19 PATIENT AFTER AN ABORTION - Pejkovska, Mirjana; Shahpaska Pejkovska, Budima; Pejkovska Ilieva, Maja; Pejkovska Ilievska, Ana (Bulgarian Association of Young Surgeons (ScopeMed), 2021)
Introduction: WHO declared the outbreak a Public Health Emergency of International Concern in January 2020 and a pandemic in March 2020. Since then, it was realized that the virus that caused the outbreak for COVID-19, is knownassevere acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Case Report: The purpose of this research is to discover the association between obstetrical condition and symptomatology of COVID-19 and to present the treatment of a patient in self-isolation after the abortion. A patient who has had an abortion, after that was diagnosed with COVID-19. Blood analyses were performed after her abortion and during and after her contagion with the virus. Analyses of d-dimmers were monitored continuously. Every symptom was carefully observed, using clinical, paraclinical, digital methods and pulls oximeter. The patient was prescribed vitamins, supplements antibiotics and immunomodulators. Patients with previous comorbidities, loss of blood, abortions, have weakened immune system. That is why they are more susceptible to infections. One of them is the coronavirus or SARS-CoV-2. Some aspects of the virus remain a mystery for medical experts. It takes a multidisciplinary approach and everyday treatment so that the patient can have elimination of the symptoms before the vaccine can be applied worldwide. Conclusion: Women who have abortions, give stillbirth sometimes can experience difficulties regarding their immune system. It is systemically and psychologically a hard moment for them an entire family. Thus the more they are prone to become specifically ill they need more time to recover.
Keywords: abortion; immune system; COVID-19